Improper preanalytical processes on peripheral blood compromise RNA quality and skew the transcriptional readouts of mRNA and LncRNA - He, Yinli; Dong, Lele; Yi, Hongyang; Zhang, Linpei; Shi, Xue; Su, Lin; Gan, Baoyu; Guo, Ruirui; Wang, Yawen; Luo, Qinying; Li, Xiaojiao (Frontiers in Genetics, 2023)
Genetic and epigenetic reprogramming caused by disease states in other tissues is always systemically reflected in peripheral blood leukocytes (PBLs). Accurate transcriptional readouts of mRNA and lncRNA in PBLs are fundamental for disease-related study, diagnosis and treatment. However, little is known about the impact of preanalytical variables on RNA quality and downstream mRNA and lncRNA readouts. In this study, we explored the impact of RNA extraction kits and timing of blood placement on PBL-derived RNA quality. A novel enhanced evaluation system including RNA yields, purity, RIN values and β-actin copies was employed to more sensitively identify RNA quality differences. The expression levels of informative mRNAs and lncRNAs in patients with chronic obstructive pulmonary disease (COPD) or triple-negative breast cancer (TNBC) were measured by qRT–PCR to investigate the impact of RNA quality on transcriptional readouts. Our results showed that the quality of RNA extracted by different kits varies greatly, and commercial kits should be evaluated and managed before batch RNA extraction. In addition, the quality of extracted RNA was highly correlated with the timing of blood placement, and the copy number of β-actin was significantly decreased after leaving blood at RT over 12 hours. More importantly, compromised RNA leads to skewed transcriptional readouts of informative mRNAs and lncRNAs in patients with COPD or TNBC. These findings have significant implications for PBL-derived RNA quality management and suggest that quality control is necessary prior to the analysis of patient mRNA and lncRNA expression.